1984
DOI: 10.1200/jco.1984.2.7.836
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of melphalan and prednisone versus melphalan, prednisone, cyclophosphamide, MeCCNU, and vincristine in untreated multiple myeloma.

Abstract: In a randomized study with 234 previously untreated patients with multiple myeloma, 129 were treated with melphalan (8 mg/m2 perorally for four days) and prednisone (40 mg/m2 perorally for seven days, both every four weeks) and 105 with melphalan and prednisone at the same doses plus cyclophosphamide (600 mg/m2 intravenously every four weeks), MeCCNU (100 mg/m2 PO every eight weeks), and vincristine (MPCCV, 0.6 mg/m2 IV every four weeks). A total of 49 (38%) of the 129 patients treated with melphalan and predn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…There continues to be a controversy regarding the optimal therapy of myeloma; however, a number of recent publications seem to confirm the results of the M-2 or similar programs especially in stage III pa tients [14][15][16][17][18]. Other prospective trials have not shown any benefit of combination therapy in myeloma [10,25], The present data confirm the earlier published Memorial Sloan-Kettering M-2 results. The present study demonstrates a response rate of 90% in 54 previously untreated patients with stages II and III disease.…”
Section: Discussionsupporting
confidence: 82%
“…There continues to be a controversy regarding the optimal therapy of myeloma; however, a number of recent publications seem to confirm the results of the M-2 or similar programs especially in stage III pa tients [14][15][16][17][18]. Other prospective trials have not shown any benefit of combination therapy in myeloma [10,25], The present data confirm the earlier published Memorial Sloan-Kettering M-2 results. The present study demonstrates a response rate of 90% in 54 previously untreated patients with stages II and III disease.…”
Section: Discussionsupporting
confidence: 82%
“…Many treatments have been effective in newly diagnosed patients with MM, including combinations of one or more alkylating agents with a glucocorticoid, the VAD regimen, or intermittent dexamethasone alone [1][2][3][4][5][6]. Among comparable patients, the response rate with VAD was approximately 15% higher than that with dexamethasone, but survival times were similar and VAD was associated with more toxicity [4].…”
Section: Discussionmentioning
confidence: 99%
“…Many treatments have been useful for patients with multiple myeloma (MM). Several studies have shown no advantage for combinations of multiple alkylating agents with or without a glucocorticoid, in comparison with melphalan-prednisone [1][2][3]. Vincristine-doxorubicin by continuous infusion with intermittent dexamethasone (VAD) has not improved the survival of newly diagnosed patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy is used to augment chemotherapy when bone or other local lesions produce symptoms. Recently, combination chemotherapy has been evaluated with results that are not significantly different from standard therapy [10,11].…”
Section: Discussionmentioning
confidence: 99%